Synthesis and Properties of Some Polythiophenes Containing Benzo[d]thiazole Heterocycle - Duong, Tran Thi Thuy; Linh, Nguyen Ngoc; Manh, Vu Quoc; Hien, Hoang Thi Thu; Dai, Do Ba; Hien, Nguyen; Chinh, Nguyen Thuy; Linh, Duong Khanh; Hung, Ha Manh; Duc, Le Minh; Hoang, Thai; Yen Oanh, Doan Thi; et al. (VNU Journal of Science: Natural Sciences and Technology, 2022)
In this paper, some new polythiophenes containing benzo[ d ]thiazole heterocycle were synthesized by the oxidative polymerization in chloroform using iron(III) chloride as a catalytic oxidant. Infrared (IR) spectroscopy and ultraviolet–visible (UV-Vis) spectroscopy analyses confirmed that the polymerization reaction successfully took place and the absorption band at 497 nm is typical for π – π * transition in the conjugated polythiophenes. The polymers are composed of relatively uniform particles using field emission scanning electron microscopy (FESEM) method. Based on thermal gravimetric analysis (TGA), the polymers had average thermal stability in the atmosphere when decomposed completely at 500 o C. The polymers exhibited fluorescence emission at about 516 nm due to the conjugated chain in the polymers.